PARTIZANSKY BASE-METAL SKARN DEPOSIT, DAL'NEGORSK ORE DISTRICT, RUSSIA: STAGES OF ORE FORMATION, MINERAL ASSEMBLAGES, AND TYPOMORPHISM OF FAHLORE - Simanenko L.F. (My University, 2006)
As indicated by mineralogical, geochemical, and structural-textural data, the base-metal skarn ore at the Partizansky deposit was formed during two stages (base-metal skarn and silver-sulfosalt), which were separated by intrusion of basaltic dikes. The bulk of the base-metal ore was deposited at the first stage, which comprises four sequential mineral assemblages: skarn-silicate, quartz-arsenopyrite, productive galena-sphalerite, and pyrrhotite-pyrite-chalcopyrite. The mineralization of the second stage was mainly confined to the upper margins of orebodies and pertains to the sulfosalt-galena-chalcopyrite assemblage, which was super-imposed on minerals of the first stage. The vertical mineralogical-geochemical zoning of the deposit is telescopic (related to the formation of the late silver-sulfosalt mineralization) and facies (typical of the early skarn and base-metal assemblages). The zoning of the skarn-silicate assemblage is expressed in the metasomatic replacement of skarn by quartz and calcite in the uppermost zone of skarn bodies and is emphasized by variation of the mineral composition throughout the skarn column, for instance, by the distinct updip enrichment of hedenbergite in manganese. The vertical zoning of the productive assemblage is emphasized by variations in the ratio of sphalerite to galena (the Pb/Zn ratio in the ore increases upward from 0.1 to 1), changes in mineral assemblages, and compositional variation of major ore-forming and minor minerals. In particular, galena from the deep levels is extremely enriched in Bi and Ag, while that from the upper levels is almost completely devoid of isomorphic admixtures. Fahlore displays updip enrichment in Sb, Ag, and Fe and corresponding depletion in Cu and Zn. The vertical chemical variations in fahlore are caused by the specific geological setting of ore deposition, the composition of the ore-forming solutions, and the physicochemical conditions of their transportation and ore deposition. © Pleiades Publishing, Inc. 2006.